2021
DOI: 10.3390/membranes11040247
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Peptide Gramicidin S Enhances Membrane Adsorption and Ion Pore Formation Potency of Chemotherapy Drugs in Lipid Bilayers

Abstract: We recently published two novel findings where we found the chemotherapy drugs (CDs) thiocolchicoside (TCC) and taxol to induce toroidal type ion pores and the antimicrobial peptide gramicidin S (GS) to induce transient defects in model membranes. Both CD pores and GS defects were induced under the influence of an applied transmembrane potential (≈100 mV), which was inspected using the electrophysiology record of membrane currents (ERMCs). In this article, I address the regulation of the membrane adsorption an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
0
6
0
4
Order By: Relevance
“…AMPs are 12-50 amino acid long peptides that have been discovered in all forms of life, including bacteria, vertebrates, and invertebrate species [9,10,[13][14][15]. Based on their physicochemical properties, they likely have a direct activity on the membrane bilayer [16,17], although sometimes they also have an intracellular target. AMPs are generally cationic and amphipathic; their net positive charge enhances electrostatic interactions with anionic bacterial membranes, while the amphipathic structure leads to membrane insertion, destabilization and disruption.…”
Section: Of 18mentioning
confidence: 99%
“…AMPs are 12-50 amino acid long peptides that have been discovered in all forms of life, including bacteria, vertebrates, and invertebrate species [9,10,[13][14][15]. Based on their physicochemical properties, they likely have a direct activity on the membrane bilayer [16,17], although sometimes they also have an intracellular target. AMPs are generally cationic and amphipathic; their net positive charge enhances electrostatic interactions with anionic bacterial membranes, while the amphipathic structure leads to membrane insertion, destabilization and disruption.…”
Section: Of 18mentioning
confidence: 99%
“…In a similar spirit, the use of conjugated antioxidants with antiretroviral drugs has been proposed to increase drug penetration into the central nervous system [599]. Additionally, peptides, including antimicrobial peptides, were proposed as an effective enhancer [600,601]. Recent MD simulations demonstrated that glycyrrhizic acid enhanced the translocation of the antiparasitic drug praziquantel through a lipid bilayer by lowering the free energy barrier associated with the hydrophobic center of the membrane along with a rearrangement of the lipid headgroups [252].…”
Section: Translocation Through the Membranementioning
confidence: 99%
“…The general drug adsorption is tested in experiments on liposomes without and with the effects of cholesterol. Modest modulation in drug adsorption has been found due to cholesterol (which naturally promotes bilayer plasticity) unlike the enhancement in drug adsorption observed recently due to bilayer physical property modulating (bilayer elasticity promoting) amphiphiles capsaicin and triton X-100 [ 51 ] and small cyclic decapeptide gramicidin S [ 52 ] in vitro constructed lipid bilayer or liposome systems.…”
Section: Discussionmentioning
confidence: 99%